Prospective feasibility and safety assessment of surgical biopsy for patients with newly diagnosed diffuse intrinsic pontine glioma. Issue 11 (5th May 2018) - Gupta, Nalin; Goumnerova, Liliana C; Manley, Peter; Chi, Susan N; Neuberg, Donna; Puligandla, Maneka; Fangusaro, Jason; Goldman, Stewart; Tomita, Tadanori; Alden, Tord; DiPatri, Arthur; Rubin, Joshua B; et al.
Abstract: Background: Diagnosis of diffuse intrinsic pontine glioma (DIPG) has relied on imaging studies, since the appearance is pathognomonic, and surgical risk was felt to be high and unlikely to affect therapy. The DIPG Biology and Treatment Study (DIPG-BATS) reported here incorporated a surgical biopsy at presentation and stratified subjects to receive FDA-approved agents chosen on the basis of specific biologic targets. Methods: Subjects were eligible for the trial if the clinical features and imaging appearance of a newly diagnosed tumor were consistent with a DIPG. Surgical biopsies were performed after enrollment and prior to definitive treatment. All subjects were treated with conventional external beam radiotherapy with bevacizumab, and then stratified to receive bevacizumab with erlotinib or temozolomide, both agents, or neither agent, based on O 6 -methylguanine-DNA methyltransferase status and epidermal growth factor receptor expression. Whole-genome sequencing and RNA sequencing were performed but not used for treatment assignment. Results: Fifty-three patients were enrolled at 23 institutions, and 50 underwent biopsy. The median age was 6.4 years, with 24 male and 29 female subjects. Surgical biopsies were performed with a specified technique and no deaths were attributed to the procedure. Two subjects experienced grade 3 toxicities during the procedure (apnea, n = 1; hypertension, n = 1). One subject experienced a neurologic deficit (left hemiparesis) that did not fully recover. Of the 50 tumors biopsied, 46 provided sufficient tissue to perform the study assays (92%, two-stage exact binomial 90% CI: 83%–97%). Conclusions: Surgical biopsy of DIPGs is technically feasible, associated with acceptable risks, and can provide biologic data that can inform treatment decisions.